Influences of dietary crude protein and stocking density on growth performance and body measurements of ostrich chicks - KHALID M. MAHROSE (Anais da Academia Brasileira de Ciências, 2019)
Abstract: Thirty-six African Black ostrich chicks were used to investigate the effects of dietary crude protein (CP) levels (180, 210 and 240 g/kg), stocking density (4.5 and 3 m2/bird) and their interactions. A factorial arrangement was used to examine the impact of treatments on growth performance and body measurements of ostrich chicks during 2 to 10 weeks of the age. Results indicated that factors studied did not change growth performance traits. The highest value of protein efficiency ratio was observed in ostrich chicks fed diet contained 240 g/kg diet. Birds fed diet contained 240 g CP /kg diet and kept at stocking density of 3 m2 per bird had numerically the highest protein efficiency ratio. Shank girth and tibiotarsus length decreased with increasing dietary CP level. Stocking density did not change values of body measurements, except tibiotarsus length at 6 weeks of age, which increased in birds kept at the lower density than the higher. Body height at 10 weeks of age was significantly affected by the interactions between dietary CP and stocking density. In conclusion, results affirmed that ostrich chicks can grow on diets containing low levels of CP (180-210 g/kg). Our results provide a comprehensive set of morphometric data for ostrich chicks as affected by the factors studied.